Effectiveness of an extraoral cold and vibrating device in reducing pain perception during deposition of local anesthesia in pediatric patients aged 3-12 years: a split-mouth crossover study - Shetty, Ashveeta; Naik, Shilpa S; Patil, Rucha Bhise; Valke, Parnaja Sanjay; Mali, Sonal; Patil, Diksha (Journal of dental anesthesia and pain medicine: JDAPM, 2023)
Local anesthetic injections may induce pain in children, leading to fear and anxiety during subsequent visits. Among the various approaches recommended to reduce pain, one is the use of a Buzzy Bee™ device that operates on the concept of gate control theory and distraction. The literature regarding its effectiveness during the deposition of local anesthesia remains limited; hence, the aim of the present study was to determine the efficacy of extraoral cold and vibrating devices in reducing pain perception during the deposition of local anesthesia. A split-mouth crossover study in which 40 children aged 3-12 years requiring maxillary infiltration or inferior alveolar nerve block for extractions or pulp therapy in the maxillary or mandibular posterior teeth were included. The control intervention involved the application of topical anesthetic gel for one minute (5% lignocaine gel), followed by the administration of local anesthetic (2% lignocaine with 1:80,000 adrenaline) at a rate of 1 ml/minute. Along with the control protocol, the test intervention involved using the Buzzy Bee™ device for 2 minutes before and during the deposition of the local anesthetic injection. The heart rate and face, legs, arms, cry, and consolability revised (FLACC-R) scale scores were recorded by the dentist to assess the child's pain perception. The mean age of the participants in Group A and Group B was 7.050 ± 3.12 years and 7.9 ± 2.65 years respectively. A reduction in the mean heart rate and FLACC-R score was observed during the deposition of local anesthetic solution in the tissues when the Buzzy Bee™ was used in both groups at different visits in the same subjects (P < 0.05) The Buzzy Bee™ device was effective in reducing the heart rate and FLACC-R scores when used during maxillary infiltration and inferior alveolar nerve block local anesthesia techniques (P < 0.05). The use of extraoral cold and vibrating devices significantly reduces pain perception during local anesthetic deposition in pediatric patients. Considering the results of this study, the device may be incorporated as an adjunct in routine dental practice while administering local anesthesia in children.